Growth Respons of Javanese Fat Tail Sheep (DEG) on Probiotic Supplementation in Diet with Different Nitrogen Source - Rina Andriati; Lalu Wirapribadi; Rr. Agustien Suhardiani; Tahyah Hidjaz (Jurnal Biologi Tropis, 2023)
The growth performance of ruminant animals depend mainly on the quantity and quality of the feed provided. In feedlot systems, the ruminant diet consists of roughages, which are in most cases preserved as native grass or hay, and concentrate feeds as Nitrogen sources. To meet their nutritional requirements and achieve the expected growth performance, these animals must be provided with adequately balanced diets. The aim of present study was to investigate the effect of probiotic supplementation in diet with different nitrogen sources on growth performance of Javanese Fat Tail Lambs. The study was conducted experimently using 48 male lambs 6-7 month of age and average body weight 18,7±2,6 kg. The probiotic tested was EM-4, a probiotic containing Lactobacillus sp, Streptomices sp. and Sacharomyces cerevisiae, with tested levels were: zero (R0, control), 0.5 ml (R1), 1.0 ml (R2), and 1.5 ml (R3) per head per day. Two types of diets were prepared, each composed of 70% native grass and 30% concentrate with different nitrogen source, both formulated to be isoprotein and isoenergy. The experimental lambs were divided into 8 groups of 6 lambs each group, each placed randomly in 48 similar individual cages. Experimental diets were given twice a day in equal portions at 08.30 in the morning and at 16.30 in the afternoon. The amount of remaining feed was measured every day at 06.00 am. Each lamb was weighed once a week for a 120-day experimental period. Data were analyzed using ANOVA according to Randomized Block Design, and further tested by the Least Significant Difference Test. The results showed that probiotic supplementation in diet had no effect (P>0.05) on Dry Matter Intake (DMI), but could increase (P<0.05) Daily Weight Gain (PBBH), Growth Rate (LP), and reduced the Feed Conversion Rate (FCR), both in the lambs fed diet with nitrogen source from Turi (Sesbania grandiflora) leaf meal (R1) and Tofu Dreg (R2). The DEG fed R1 showed a 7.7% higher PBBH than those of fed R2. The probiotic supplementation on R1 and R2 gave the optimum effect on PBBH and FCR at the supplementation level of 1.5 ml/head/day.